Grade 11 learner's speaking skills in Sepedi home language classroom at Bogwasha Circuit, in Sekhukhune East District, Limpopo Province, South Africa - Matlebjane, Piet Morokwe (My University, 2024)
South African schools under the Department of Basic Education (DBE) have language education as part of the curriculum. The DBE introduced the study of home languages as a measure to preserve culture, traditions and values of indigenous languages and drive transformation agenda. Sepedi Home Language (SEPHL) is a subject that is taught in most Bapedi communities in the Limpopo Province and partly in some provinces such as Gauteng and Mpumalanga. The subject is concerned with language education of the SEPHL. It is predominantly taught as a home language in schools. According to Education (2019), home languages refer to a learners’ mother tongue or a home language that is spoken in a particular setting and promotes abstract reasoning. The aim of this study is to investigate the speaking skills of learners in learning to speak fluently in Sepedi Home Language. The study draws from the theory of phenomenology. The framework is concerned with traditions of philosophy which aims to reflect on human experience (Irene & Albine, 2018). The approach attempts to explain language experiential meanings as they occur and are shaped by language, cognitive sensibilities, social, personal, and cultural preunderstandings (Van Manen and Adams, 2018). The study employed the qualitative research methodology as the founding foundation. The study constitutes a population of 32 schools from which 2 were sampled. This study investigated the speaking skills of learners in learning to speak fluent SEPHL in Bogwasha Circuit Sekhukhune East District in Limpopo, South Africa. Learners are expected to perform exceptionally well in-home languages as they are mainly the languages, they speak at their homes regularly. However, with the dominance of English as a prestigious and global language predominantly used as a medium of instruction, learners often struggle with their home languages when it comes to acquiring vital language skills such as speaking, reading and writing. The study found that Sepedi Home Language speaking skills are adversely influenced by various factors such as technology, dialect, influence of other languages, Language use and code-switching in the classroom.
Thesis (M. Ed. (Language Education)) -- University of Limpopo, 2024
Keywords: Grade 11 learners; Code-switching; Home languages; Indigenous languages; Influence; Language learning; Language use; Mother tongue; Phenomenology; Sepedi home language; Sepedi language; Sepedi language -- Study and teaching; Language and languages -- Study and teaching; Language and education